ANALISIS KESALAHAN SISWA PADA PENYELESAIAN SOAL CERITA BERDASARKAN TAHAPAN NEWMAN - Dinnullah, Riski Nur Istiqomah; Noni, Eudesiana; Sumadji, Sumadji (Institut Agama Islam Negeri (IAIN) Tulungagung, 2019)
This study aims to describe the analysis of student mistakes based on the stages of Newman in solving the Pythagorean theorem material story problems. This type of research is descriptive with a qualitative approach. The subjects of this study were students of class VIII A PGRI 6 SMP Malang, totaling 28 students in the 2018/2019 school year. Data analysis techniques include data reduction, data presentation and conclusion drawing. Meanwhile, checking the validity of the data using the technique of triangulation of sources in the form of in-depth interviews with 3 students of class VIII A selected based on high, medium, and low abilities. The results showed that at the stage of reading subject A5 made a mistake in question number 3. In the understanding stage, an error in problem number 1 was made by subjects A29, A7, A11, and A5, while error number 2 was subject A21, A7, and, which made a mistake in question number 3 namely, A6, A29, A7, and A5. At the transformation stage subjects A5, and A11 made mistakes on questions number 2 and 3. In the process skills stage subjects A5 made mistakes on questions number 2, and subjects A21, A6, A7, A11, and A5 made mistakes on questions number 3. Meanwhile , subjects who make mistakes at the writing stage of the final answer are A29, A7, A11, and A5.